Interpretation and application of the offside law by expert assistant referees: Perception of spatial positions in complex dynamic events on and off the field - Gilis, B.; Helsen, W. F.; Catteeuw, P.; van Roie, E.; Wagemans, J. (Journal of Sports Sciences, 2009)
Baldo et al. (2002) and Helsen et al. (2006) considered the flash-lag effect to explain errors made by assistant referees when judging offside in association football. The main aims of the present study were as follows: (1) to determine whether the flash-lag effect emerges in offside situations on the field of play or off the field when presented as computer animations or as video footage of real-life matches; (2) to examine offside decision-making errors in two standards of assistant referee - international FIFA and Belgian national referees. The results support the flash-lag hypothesis in several ways. First, both the FIFA and Belgian assistant referees were more likely to make errors by raising their flag when they had to assess offside situations on the field of play and when presented as three-a-side computer animations. Second, more flag errors were made when the defender moved in the opposite direction to that of the attacker. Third, the strategy of raising the flag in case of doubt was not observed when an interpretation of the offside law had to be made about the involvement of play of an attacker. Future research is needed to examine the extent to which on- and off-the-field training sessions can be used as training tools to improve offside decision-making.